KONVERGENSI TEOLOGIS: Analisis intertekstual antara Al-Qur'an dan Bibel dalam Tafsir al-Qur’an karya Zainuddin Hamidy dan Fachruddin HS - Bana, Sarifa Aliyal; Kamil, Ahmad Zaidanil (Kontemplasi: Jurnal Ilmu-Ilmu Ushuluddin, 2023)
The discourse of interpreting the Qur'an using the Bible is a controversial topic among mufassirs, especially among contemporary mufassirs in Nusantara. This article aims to discuss the intertextuality interpretation of Zainuddin Hamidy and Fachruddin Hs in Surah Al-Baqarah, especially in the context of using the Bible as a reference in understanding the Qur'an. This intertextuality approach raises interesting questions about how two different scriptures can influence the understanding and interpretation of the Qur'an, as well as its implications for understanding Islam in Indonesia. The research method used in this article is library research with content analysis technique, which allows in-depth analysis of the content of the tafsir al-Qur'an by Zainuddin Hamidy and Fachruddin Hs. By using Edip Yuksel's cross reference theory, the results of this study show that the Biblical quotations set forth by Zainuddin Hamidy and Fachrudin HS in their works are influenced by previous books used as references. There are two intertext models used by Zainuddin Hamidy and Fachrudin HS in Q.S al-Baqarah including: First, the comparative model by comparing the Bibel with the Qur'an or Islamic teachings. Second, the reference model that serves to show the similarity of the theme of the conversation between the Qur'an and the Bibel.